2005
DOI: 10.1128/aem.71.7.3653-3658.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 26-Oxygenosterols from Ganoderma lucidum and Their Activity as Cholesterol Synthesis Inhibitors

Abstract: Ganoderma lucidum is a medicinal fungus belonging to the Polyporaceae family which has long been known in Japan as Reishi and has been used extensively in traditional Chinese medicine. We report the isolation and identification of the 26-oxygenosterols ganoderol A, ganoderol B, ganoderal A, and ganoderic acid Y and their biological effects on cholesterol synthesis in a human hepatic cell line in vitro. We also investigated the site of inhibition in the cholesterol synthesis pathway. We found that these oxygena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 26 publications
1
51
0
5
Order By: Relevance
“…The active GA-H is hydroxylated at position 3 and GA-A at position 7 and 15; whereas inactive GA-F is not hydroxylated. In addition, other triterpenes with hydroxyl or acetoxy groups at the positions 3, 7 and/or 15 such as ganoderic acid C1, ganoderic acid C2 (30), ganoderic acid D (31), ganoderic acid T (20), ganoderic acid X (19), ganoderic acid Y (32), ganoderiol A (31), ganoderol B (32,33), lucidumol B and ganodermadiol (30,31) were shown to have inhibitory biological activity. Shiao (34) demonstrated that several Ganoderma triterpenes with hydroxyl or acetoxy groups in these positions were cytotoxic to hepatoma cells and inhibited histamine release, cholesterol synthesis, and farnesylation of Ras protein.…”
Section: Discussionmentioning
confidence: 99%
“…The active GA-H is hydroxylated at position 3 and GA-A at position 7 and 15; whereas inactive GA-F is not hydroxylated. In addition, other triterpenes with hydroxyl or acetoxy groups at the positions 3, 7 and/or 15 such as ganoderic acid C1, ganoderic acid C2 (30), ganoderic acid D (31), ganoderic acid T (20), ganoderic acid X (19), ganoderic acid Y (32), ganoderiol A (31), ganoderol B (32,33), lucidumol B and ganodermadiol (30,31) were shown to have inhibitory biological activity. Shiao (34) demonstrated that several Ganoderma triterpenes with hydroxyl or acetoxy groups in these positions were cytotoxic to hepatoma cells and inhibited histamine release, cholesterol synthesis, and farnesylation of Ras protein.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their significant medicinal importance, mushrooms of the Ganoderma species have gained noticeable interest from biomedical researchers. A number of studies have revealed the medicinal values of Ganoderma mushrooms against various life-threatening diseases and health complications like cancer, immunodeficiency, cardiovascular complications, diabetes, hepatic disease, neurodegeneration, and infectious disease (Hajjaj et al, 2005;Paterson, 2006;Ma et al, 2011;Chu et al, 2012;Tie et al, 2012;Xiao et al, 2012;Boh, 2013;Wang et al, 2013;Wu et al, 2013;Yue et al, 2013). There are numerous variations in the size, shape, and color of Ganoderma mushrooms, and they differ in biological properties as well.…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderma extracts and spores oil 4 /well) were seeded into 96-well plates and treated with a series of concentrations of Ganoderma spores oil (0.31, 0.63, 1.25, 2.5, 5 and 10 mg/ml) for 24 h. Control cells were exposed to double distilled water containing the same concentration of Tween 80. Subsequently, 20 µl of 5 mg/ml MTT (Sigma-Aldrich, St. Louis, MO, USA) was added to each well and incubated for 4 h. The dark blue formazan crystals were solubilized in lysis buffer containing 10% sodium dodecyl sulfate (SDS), 5% isobutyl alcohol and 12 mmol/l HCl, and the optical density (OD) was detected at 492 nm with a spectrophotometer.…”
Section: Antitumor Effects and Mechanisms Ofmentioning
confidence: 99%
“…Modern pharmacological and clinical studies have confirmed that Ganoderma contains abundant biologically active substances in its fruiting body, mycelia and spores, and possesses variable functions, including immunomodulation, anti-aging, reducing blood lipids, anti-viral and anti-tumor activities (1)(2)(3)(4)(5)(6). The present study examined the antitumor activity of a mixture of aqueous and ethanol extracts of the Ganoderma fruiting body and Ganoderma spores oil, which was extracted from broken spores by supercritical CO 2 extraction technology and explored the possible underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%